Anodically grown functional oxide nanotubes and applications. (24th October 2016) - Rao, B. Manmadha; Torabi, Aida; Varghese, Oomman K.
Abstract: Abstract : Among various material nanoarchitectures, the nanotube geometry has received incredible attention due to the unique properties provided by its high surface area as well as nanoscale wall thickness and the availability of a variety of techniques to fabricate them. Since the beginning of this century, anodization has emerged as one of the most effective techniques for the fabrication of functional oxide nanotubes. Oxide nanotubes of a number of metals and alloys have been developed using this versatile technique. We review here the research activities on anodic nanotubes of various binary, ternary, and multinary materials and their selected applications.